Assessing the effectiveness of recent pension reforms: The French experiment - Bravo, J. M.; Ayuso, M.; El Mekkaoui, N. (Socio-Economic Planning Sciences, 2025)
Reforming public and private pension systems to address the challenges posed by population ageing and a range of economic, labour market, social, political, geopolitical, technological, legal, and regulatory shocks remains a major policy priority for many countries. A widely supported response has been to raise minimum and statutory retirement ages and restrict early exit pathways. These measures aim to boost labour force participation and employment among older individuals, stimulate potential GDP growth and consumption, ease pressure on social security systems, and improve public finances. However, it remains uncertain whether pension reforms alone can prevent a decline in the relative size of the labour force or ensure intergenerational fairness. This paper assesses the effectiveness of recent retirement age reforms in France in stabilising the old-age dependency ratio and securing long-term financial sustainability. It also examines whether these reforms promote intergenerational equity. The findings suggest that the reforms fall short of offsetting the projected decline in the labour force, achieving fairness across generations, and maintaining fiscal balance. The results underscore the need for a holistic and dynamic approach to retirement age policy design.